2017
DOI: 10.1007/s10068-017-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of washed and unwashed tilapia (Oreochromis mossambicus) fish meat: effect of sucrose and sorbitol

Abstract: In the present study, the dynamic viscoelastic behavior (DVB) and flow behavior of fresh tilapia (Oreochromis mossambicus) meat containing cryoprotectants were evaluated with and without water washing. The DVB profile of washed meat with 4% sucrose and sorbitol indicated the maximum structure buildup reaction up to 56.8°C; thereafter, hydrophobic interactions leading to decreased gelation were suppressed. In both the samples, there was no clear indication of the sol-gel transition temperature. In flow-profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, in some specific cases, rheological measurements have been successfully related to food preparation. The storage shear modulus of cod flesh 13 and surimi 19 was found to increase during cooking when the internal temperature of the sample was between 50 and 70 o C. The rheological properties of gelled desserts has been compared with the consumer appreciation 17 , and it was observed that the elastic properties and the yield stress should neither be too large or too small.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some specific cases, rheological measurements have been successfully related to food preparation. The storage shear modulus of cod flesh 13 and surimi 19 was found to increase during cooking when the internal temperature of the sample was between 50 and 70 o C. The rheological properties of gelled desserts has been compared with the consumer appreciation 17 , and it was observed that the elastic properties and the yield stress should neither be too large or too small.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al (2020) considered the use of customized shapes for chicken meat-based products and conducted feasibility studies on 3D-printed nuggets [ 23 ]. Murthy et al (2017) determined the effect of sucrose and sorbitol on the rheological properties of washed and unwashed tilapia ( Oreochromis mossambicus ) fish meat [ 24 ]. Nelson et al (2020) proposed a mathematical model for the meat cooking process [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the technology of products from minced fish is promoted by the wide possibilities of carrying out various modifications on its basis with the aim of regulating nutritional value and creating enriched and functional food products. The traditional raw materials for minced meat production are fish with predominantly light muscle tissue, low-fat content, and high content of myofibrillar proteins (Hagen and Johnsen, 2016; Murthy et al, 2017;Gonçalves and Salas-Mellado, 2018;Cardoso et al, 2019;Chen et al, 2020;Gu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%